Burocrazia e fisco a Napoli tra XV e XVI secolo La Camera della Sommaria e il Repertorium alphabeticum solutionum fiscalium Regni Siciliae Cisfretanae - Delle Donne, Roberto (Reti Medievali E-Book, 2012)
The book outlines the processes of "bureaucratization" of the financial offices of the Kingdom of Naples, dwelling on the administrative praxis of the Regia Camera della Sommaria. It starts from the critical edition of Repertorium Alphabeticum Solutionum Fiscalium Regni Siciliae, a XVIth century manuscipt produced by Sommaria, rich with information about the whole area of Southern Italy, which became particularly precious after the destruction of the Aragonese documentation of the State Archive in Naples in the fire of September 1943. The research originates in the "slow" reading of a text, in the inquiry on its characteristics, structure, sources, context, events which led to its writing and on the practices of administrative work which it was to describe and orientate. This volume reconstructs also the long process which led to the Sommaria office, between the last decades of the XIIIth century and the first of the XVth century, its competences and working from the Aragonese age, up to the middle of the XVIth centuryt, on the basis of published and unpublished sources, kept in various Italian and European archives and libraries, in a costant comparison with the wide international bibliography.